Study of ceruloplasmin in subjects our midst - Carpio Meléndez, Percy (1968)
The physiological role of ceruloplasmin and pathogenesis of its metabolic derangements linked to copper, is still unknown. Wilson's disease is the only disease in man due to a disorder of copper metabolism whose intimate nature is not yet clarified. The usual explanation of the phenomenon (11) observed in the disease is that the patient is unable to synthesize ceruloplasmin when the abnormal gene occurs in the form homociqótica. The increase in copper absorption through the gut and deposit in tissues to toxic levels is said to be secondary to impaired synthesis of ceruloplasmin. This explanation is not consistent, because some patients with Wilson's disease have normal levels of ceruloplasmin or approximately normal.